Utilizing of using blocks in the stilling basin and their effects on characteristics of the hydraulic jump - Hadi, Humam Amer; Al-Qaisi, Atheer Zaki; Akhtari, Ali Akbar (Al-Nahrain Journal for Engineering Sciences, 2026)
The stilling basin is a frequently used energy dissipators that converts supercritical flow from a dam's spillway into subcritical flow that is in compatible with the downstream river regime. They serve to prevent scouring, which happens when high-velocity water enters the dam's downstream reach. This scouring not only seriously erodes the downstream area but also damages the dam's foundation. In this research, the behavior of blocks of stilling basin and spillway toe in reducing energy losses and the longitudinal hydraulic jump toe position is evaluated. This research includes two cases ; case1 is a spillway and stilling basin without blocks, and case2 which is a spillway and stilling basin with chute blocks and middle blocks. By increasing the discharge from 0.010 m3/s to 0.020 m3/s, the difference in the dissipation energy for case1 and case2 are (17.6%, 24.7%) respectively, and that the percentage of decrease in the longitudinal hydraulic jump toe position is (83.94%, 85.90%, 86.30%, 87.20%, 88.39%, 87.58%, 80.64%, 77.94%) for the discharges tests from ( 0.010 m3/s to 0.017 m3/s). As a results, The using of blocks in stilling basin and spillway led to a rise in relative energy dissipation and decrease the longitudinal hydraulic jump toe position of stilling basins.